2002
DOI: 10.1149/1.1512671
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of the Cd Underpotential Deposited Layer Formed on an Au(111) Substrate

Abstract: The surface-normal structure of a Cd layer formed on an Au(111) substrate using underpotential deposition (UPD) in a sulfuric acid solution has been investigated by specular X-ray reflectivity measurements. The measurements were carried out for the Cd UPD layers which were formed at the first and second UPD potential in electrolytic solutions of 1 mM CdSO4 with 10 mM and 100 mM H2SO4. In all cases, a Cd atomic layer is positioned on the Au(111) surface, which is similar to the reconstructed structure, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Since the Os islands are morphologically rough (see smaller-scale images below), the precise height of Os was not determined well enough to distinguish Os from Au based only on the apparent height. Indeed, alloy formation with Au(111) has been observed previously after the electrodeposition of Pb, 34,35 Cd, [36][37][38][39][40][41][42] and Sb [43][44][45][46] noble metal Pt was deposited on Au(111) at room temperature and formed a 0.03 ML alloy followed by the formation of mixed Pt-Au islands. 47 Thus, the formation of an Au-Os alloy seems possible and it is the best explanation for the unexpectedly high coverage of islands.…”
Section: Resultsmentioning
confidence: 86%
“…Since the Os islands are morphologically rough (see smaller-scale images below), the precise height of Os was not determined well enough to distinguish Os from Au based only on the apparent height. Indeed, alloy formation with Au(111) has been observed previously after the electrodeposition of Pb, 34,35 Cd, [36][37][38][39][40][41][42] and Sb [43][44][45][46] noble metal Pt was deposited on Au(111) at room temperature and formed a 0.03 ML alloy followed by the formation of mixed Pt-Au islands. 47 Thus, the formation of an Au-Os alloy seems possible and it is the best explanation for the unexpectedly high coverage of islands.…”
Section: Resultsmentioning
confidence: 86%
“…25 According to results reported for Cd/Au(111), the coverage of Cd varied between 0.4 and 0.66, which is substantially higher than that (θ ) 0.17) of Cd/Rh(111). 31,32 This thought could also hold for the coadsorbed anions of (bi)sulfate, whose coverage differ on these two surfaces. 31,32 These anionic species which are intermediates in the interactions between Cd adatoms also contributed to the arrangements of Cd deposit.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 This thought could also hold for the coadsorbed anions of (bi)sulfate, whose coverage differ on these two surfaces. 31,32 These anionic species which are intermediates in the interactions between Cd adatoms also contributed to the arrangements of Cd deposit.…”
Section: Discussionmentioning
confidence: 99%
“…The specific adsorption of sulfate anions during the Cd UPD on Au(111) was also suggested on account of specular X-ray reflectivity results. [12] It was demonstrated that the coverage of the Cd UPD layer increases with increasing sulfate anion solution concentration, but from these experiments the involved surface alloying was not clear. A surface alloy formation process was observed [13 -16] in the system Au(100)/Cd 2+ , SO 4 2− and it was concluded that, in this case, the Au-Cd surface alloy is formed during the UPD phenomenon probably by a turnover process between the adsorbed Cd atoms and the underlying Au atoms, with a subsequent solid-state diffusion of these atoms through the alloyed phase.…”
Section: Introductionmentioning
confidence: 88%